2016
DOI: 10.1186/s12878-016-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in achieving a target international normalized ratio for deep vein thrombosis among HIV-infected patients with tuberculosis: a case series

Abstract: BackgroundTuberculosis (TB) and HIV are among the risk factors for deep vein thrombosis (DVT). There are several challenges in the management of DVT patients with TB-HIV co-infection including drug-drug interactions and non-adherence due to pill burden.MethodsHIV infected patients starting treatment for TB were identified and followed up two weekly. Cases of DVT were diagnosed with Doppler ultrasound and patients were initiated on oral anticoagulation with warfarin and followed up with repeated INR measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…[106] In a Ugandan case series, patients concomitantly prescribed rifampicin, antiretroviral therapy, and warfarin had highly labile INRs and warfarin dose requirements, and it was not possible to predict the course of INR results in any individual patient. [107] In Kenya, VTE patients with advanced HIV and tuberculosis required a median 8 additional clinic visits to achieve or maintain a therapeutic INR. [108] Despite widespread herbal medicine use in SSA [109,110] there is very little data on how this influences anticoagulation.…”
Section: Patient-related Challengesmentioning
confidence: 99%
“…[106] In a Ugandan case series, patients concomitantly prescribed rifampicin, antiretroviral therapy, and warfarin had highly labile INRs and warfarin dose requirements, and it was not possible to predict the course of INR results in any individual patient. [107] In Kenya, VTE patients with advanced HIV and tuberculosis required a median 8 additional clinic visits to achieve or maintain a therapeutic INR. [108] Despite widespread herbal medicine use in SSA [109,110] there is very little data on how this influences anticoagulation.…”
Section: Patient-related Challengesmentioning
confidence: 99%
“…The burden of HIV and tuberculosis (TB) is high in sub-Saharan Africa [6]. Patients on warfarin who are HIV positive and/or have TB require multiple concomitant medicines, which may interact with warfarin and complicate warfarin dosing and dose adjustment [7].…”
Section: Introductionmentioning
confidence: 99%
“…ARV drugs have variable effects on warfarin blood levels, some causing an increase in levels and some a decrease. Sekaggya et al 17 demonstrated this in a case series of HIV-infected patients being treated for tuberculosis. Jong et al 4 demonstrated lower levels of the von Willebrand factor, factor VIII, D-dimer and endogenous thrombin potential in HIV-infected patients on ARV drugs.…”
Section: Discussionmentioning
confidence: 83%
“…The development of a warfarin dosing algorithm for HIV-infected persons would be difficult and complex because of the multiple influences that may be operating. 14 17 These include genetic factors, the hypercoagulable state, pertinent infections and malignancies, and the effect of multiple drugs on the cytochrome P450 2C9 system. These diverse effects on warfarin dosage are probably reflected in the wide range of SD in this study as shown in figure 1 .…”
Section: Discussionmentioning
confidence: 99%